2017
DOI: 10.1002/jcb.26369
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of purine‐rich element binding protein B as a novel biomarker in acute myelogenous leukemia prognostication

Abstract: Acute myelogenous leukemia (AML) is an aggressive hematologic cancer characterized by infiltration of proliferative, clonal, abnormally differentiated cells of myeloid lineage in the bone marrow and blood. Malignant cells in AML often exhibit chromosomal and other genetic or epigenetic abnormalities that are useful in prognostic risk assessment. In this study, the relative expression and novel single-stranded DNA (ssDNA) binding function of purine-rich element binding proteins A and B (Purα and Purβ) were syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…PURB has been reported to be a transcriptional co-activator and binds to the single strand of the repeated purine-rich element PUR which is present in promoter regions and as such has been implicated in transcriptional control. PURB plays different roles in many physiological and pathological processes [51][52][53] . For example, PURB has been shown to be overexpressed in several different cancer types 54 .…”
Section: Discussionmentioning
confidence: 99%
“…PURB has been reported to be a transcriptional co-activator and binds to the single strand of the repeated purine-rich element PUR which is present in promoter regions and as such has been implicated in transcriptional control. PURB plays different roles in many physiological and pathological processes [51][52][53] . For example, PURB has been shown to be overexpressed in several different cancer types 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Two other proteins of interest that bind to single-stranded DNA in the nucleus are encoded by Purb and Fubp1. In the first case, purine-rich element-binding proteins A and B are implicated in the regulation of gene expression at both transcription and translation levels, the highest levels of PURB being observed in myeloid cells from patients with primary acute myelogenous leukemia displaying risk factors forecasting a poor prognosis [63]. At the end of the 2010s, FUBP1 represented one of the fifty types of specific factors already reported to regulate c-myc transcription [64], whose overexpression was associated with the regulation of proliferation and migration in liver cancer cells [65].…”
Section: Discussionmentioning
confidence: 99%
“…42 Fluid-phase Purβ WT and variant proteins were evaluated at a limiting protein concentration of 1.0 nM in the primary binding step in the ELISA. Solutions of 300 μg/mL protein in aqueous buffer containing SYPRO Orange were heated in 1°C increments/min and changes in fluorescence were monitored over time.…”
Section: Dna-binding Properties Of Purβ Variantsmentioning
confidence: 99%
“…Additionally, a purine-rich element from the 5′-flanking region of the human MYC gene (PUR24-bF) was utilized as an independent positive control for Purβ-ssDNA interaction. 42 Fluid-phase Purβ WT and variant proteins were evaluated at a limiting protein concentration of 1.0 nM in the primary binding step in the ELISA. Subsequent antibody-based detection of solid-phase nucleoprotein complexes revealed that the interaction of Purβ P223L and R297Q with purine-rich ssDNA sequences was indistinguishable from wild-type Purβ ( Figure 5B).…”
Section: Dna-binding Properties Of Purβ Variantsmentioning
confidence: 99%